Praxis of Critical Literacy: Pragmatic Utilization of Theoretical Tensions - Takeda, Yuya (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2022)
The purpose of this paper is to re-examine the foundation of critical literacy. I claim that critical literacy should be conceived as praxis rather than a unified theory. This is because the foundation of critical literacy includes diverse philosophical positions with some disagreements between them. When critical literacy is treated as a unified theory, such internal contradictions implode the theory. Instead, by conceiving it as praxis, even those theoretical tensions can be rendered generative for insatiable reading of the wor(l)d. To demonstrate this, I juxtapose Marxist/Freirean approach and Foucauldian approach to critical literacy. The former approach solidifies the battle ground for critical projects by “naming” the wrongs of the world, while the latter dissipates such identification by inserting divergence and discontinuity into the narratives. I discuss the kinds of critical literacy questions these two approaches enable us to ask, and generate new questions that emerge from the theoretical tensions.